2016
DOI: 10.1371/journal.ppat.1005472
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated and Total HIV-1 DNA Predict Ex Vivo Viral Outgrowth

Abstract: The persistence of a reservoir of latently infected CD4 T cells remains one of the major obstacles to cure HIV. Numerous strategies are being explored to eliminate this reservoir. To translate these efforts into clinical trials, there is a strong need for validated biomarkers that can monitor the reservoir over time in vivo. A comprehensive study was designed to evaluate and compare potential HIV-1 reservoir biomarkers. A cohort of 25 patients, treated with suppressive antiretroviral therapy was sampled at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 45 publications
9
88
1
Order By: Relevance
“…When compared with alternative measurements of reservoir size, the HIV RNA/Gag assay most closely mirrors findings using the VOA, where the minimum size of the replication-competent reservoir is estimated to be 1 per million resting CD4 (1.4 in our cohort), 100–1000 fold less than that measured by integrated DNA. In addition, both the reservoir size as measured by the HIV RNA/Gag assay here and the VOA, shown previously (Kiselinova et al, 2016), correlate with the reservoir measured by integrated HIV DNA. The advantage of the HIV RNA/Gag assay is the direct detection of HIV-infected cells, allowing phenotyping, which is not possible with the VOA.…”
Section: Discussionsupporting
confidence: 77%
“…When compared with alternative measurements of reservoir size, the HIV RNA/Gag assay most closely mirrors findings using the VOA, where the minimum size of the replication-competent reservoir is estimated to be 1 per million resting CD4 (1.4 in our cohort), 100–1000 fold less than that measured by integrated DNA. In addition, both the reservoir size as measured by the HIV RNA/Gag assay here and the VOA, shown previously (Kiselinova et al, 2016), correlate with the reservoir measured by integrated HIV DNA. The advantage of the HIV RNA/Gag assay is the direct detection of HIV-infected cells, allowing phenotyping, which is not possible with the VOA.…”
Section: Discussionsupporting
confidence: 77%
“…Similar results were recently reported by Kiselinova et al (11). More recently, Noel et al also reported that the low level of total HIV DNA in cells from long-term nonprogressors (LTNPs) correlated with the low efficiency of virus production after activation ex vivo (58).…”
Section: Dna Load In Resting Cd4supporting
confidence: 86%
“…Two comprehensive studies have compared a panel of HIV reservoir biomarkers (9,11), but such studies are limited by the fact that large amounts of blood are needed to test all markers in a given patient. The different approaches may be used differently according to the issue in question, such as the overall level of HIV infection in the body, viral persistence, reservoir activity, or the role of the HIV reservoir in maintaining immune activation.…”
Section: Place Of Total Hiv Dna Among Markers Used To Evaluate Hiv Rementioning
confidence: 99%
See 1 more Smart Citation
“…Although measurement of total HIV-1 DNA levels may take into account many copies of replication-deficient viruses, it is likely that under conditions of very low levels of viral replication, as in HICs, differences in the levels of HIV-1 DNA probably maintain proportionality between replication-competent and noncompe-tent proviruses, as recently observed in treated patients (54). This assumption is supported, despite limitations in the total numbers of CD4 ϩ T cells tested, by the direct correlation between the levels of cell-associated HIV-1 DNA and HIV-1 reactivation, measured by determination of the levels of HIV-1 RNA or p24 production in culture supernatants, that was found when CD4 ϩ T cells were split into parallel cultures and were subjected to different repeated stimuli (with polyclonal or allogeneic stimuli or the provision of latency-reversing agents).…”
Section: Discussionmentioning
confidence: 99%